2021
DOI: 10.1364/oe.420003
|View full text |Cite|
|
Sign up to set email alerts
|

Multifunctional metalens generation using bilayer all-dielectric metasurfaces

Abstract: Optical metasurfaces exhibit unprecedented ability in light field control due to their ability to locally change the phase, amplitude, and polarization of transmitted or reflected light. We propose a multifunctional metalens with dual working modes based on bilayer geometric phase elements consisting of low-loss phase change materials (Sb2Se3) and amorphous silicon (a-Si). In transmission mode, by changing the crystalline state of the Sb2Se3 scatterer, a bifocal metalens with an arbitrary intensity ratio at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…They have already been applied in many applications, particularly in metalenses 2,3 , holograms [4][5][6] , vortex beam generators [7][8][9] and so on. Metalenses with multi-foci are practically useful [10][11][12][13] due to their ultrathin configuration that can be integrated into miniature optical systems for multiple functions, and by far a group of multifocal metalenses have been reported [14][15][16][17][18][19][20] . Free control and continuous zooming of each foci from multifocal metalenses are of important use in realistic applications, and we propose a tunable bifocal metalens (TBML) in this study, with two continuous-zoom foci is proposed as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…They have already been applied in many applications, particularly in metalenses 2,3 , holograms [4][5][6] , vortex beam generators [7][8][9] and so on. Metalenses with multi-foci are practically useful [10][11][12][13] due to their ultrathin configuration that can be integrated into miniature optical systems for multiple functions, and by far a group of multifocal metalenses have been reported [14][15][16][17][18][19][20] . Free control and continuous zooming of each foci from multifocal metalenses are of important use in realistic applications, and we propose a tunable bifocal metalens (TBML) in this study, with two continuous-zoom foci is proposed as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…To date, most of the reported bilayer dielectric metasurfaces were demonstrated for operation in the near-infrared region and much of the effort were mainly devoted to monochromatic aberration correction, [33][34][35] multiwavelength control, [36][37][38] and light path or polarization control, [39][40][41][42] among others. [43][44][45] However, their potential in full-space light control remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…So far, there have been several ways to achieve this. The relative intensity ratio of the two focal points can be adjusted by varying the size of the unit dimensions [48], changing the crystalline fraction of the phase change material [49], and controlling the diversity of the incident beam helicity [50]. The bilayer metalens designed in this paper can utilize different crystalline fractions of phase change materials to achieve continuous zooming of the focus and can also control the intensity contrast of the bifocals by changing the phase difference between a pair of orthogonally polarized incident waves.…”
Section: Introductionmentioning
confidence: 99%